Arylnaphthalene lactone analogues: synthesis and development as excellent biological candidates for future drug discovery. Issue 17 (6th March 2018) - Zhao, Chuang; Rakesh, K. P.; Mumtaz, Saira; Moku, Balakrishna; Asiri, Abdullah M.; Marwani, Hadi M.; Manukumar, H. M.; Qin, Hua-Li
Abstract : A review of recent developments in the synthesis and biological applications of arylnaphthalene lactones analogs. Abstract : Arylnaphthalene lactones are natural products extracted from a wide range of different parts of plants. The progressing interest in the synthesis of these compounds is due to their significant biological activities, which have made them potential candidates in drug discovery and development. This review mainly covers recent developments in the synthesis and biological applications of arylnaphthalene lactone analogs.